Bonding in Pursuit of Policy Goals: How MPs Choose Political Parties in the Legislative State of Nature. Issue 3 (7th January 2019) - Sieberer, Ulrich; Herrmann, Michael
Abstract : How do MPs in nascent legislatures choose a political party? We argue that MPs self‐select into groups of like‐minded colleagues to achieve favored policy outputs. MPs identify colleagues with similar preferences based on observed behavior and informative signals such as socioeconomic status, cultural background, and previous political experience. We test this explanation in the first democratically elected German parliament, the Frankfurt Assembly of 1848, that developed a differentiated party system in the absence of electoral and career incentives. Our statistical analysis shows that MPs were significantly more likely to join parties that were similar to them with regard to ideology, age, regional provenance, confession, noble status, and previous parliamentary experience. Qualitative evidence suggests that major changes in the party system were driven by disputes over policy. Our findings are particularly important for countries with more turbulent paths towards parliamentarization than those witnessed by archetypical cases like Britain or the United States.